EFEKTIFITAS TINGKAT PENCAHAYAAN ALAMI DAN PENCAHAYAAN CAMPURAN PADA RUANG PERKULIAHAN DI UIN SUMATERA UTARA - Mulkan Iskandar Nasution; Zubair Aman Daulay; Rini Rahmadani Tampubolon (Universitas Riau, 2022)
Lighting is part of the main factor in a building design, because it affects the activities of user in the room. The purpose of this study is knowing the level of illumination level in the classroom of the Faculty of Science and Technology, UIN North Sumatra. The study was conducted by measuring the level of natural lighting, mixed lighting levels and optimization of mixed lighting levels in classrooms 306 and 308 with reference to SNI 6197-2011 which is 350 lux. Size of classroom 306 length 8.70 m, width 8 m, height 2.80 m, while classroom 308 length 8.40 m, width 8.12 m, height 2.80 m. The natural lighting source comes from the sun (window openings), while the mixed lighting source comes from the sun (window openings) plus 36 Watt TL lamps. The measurement of lighting levels is carried out using the GM1040C luxmeter measuring instrument with 25 measurement points in accordance with the SNI 7062-2019. The measurement results for natural lighting levels, namely 161.38 lux and 206.9 lux, are not in accordance with the lighting standard, which is 350 lux, while for mixed lighting, namely 720 lux and 975 lux and optimization of mixed lighting, namely 406.68 lux, 405.72 lux and 479.28 lux and 472.44 lux are in accordance with the lighting standard of 350 lux.